THE ROLE OF RESORT AREAS IN THE SYSTEM OF PROTECTED NATURAL AREAS - Alloberdiyeva Durdona Oktamjon qizi (PEDAGOGS, 2025)
Annotation. This article analyzes the ecological and social significance of resort zones within the system of protected natural areas. Resort zones are specially protected territories that not only provide opportunities for rehabilitation, treatment, and recreation, but also serve to preserve unique natural resources. They play a key role in maintaining biodiversity, protecting natural landscapes, and ensuring ecological sustainability. The article examines the legal status of resort zones based on the Laws of the Republic of Uzbekistan “On Resorts” and “On Protected Natural Areas,” as well as the ecological restrictions, control mechanisms, and management systems applicable to them. Furthermore, it emphasizes the importance of sustainable tourism, the development of health infrastructure, and the preservation of ecological balance in the development of these zones.